2021
DOI: 10.1111/bcpt.13687
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety and bioequivalence of two formulations of progesterone soft capsule in healthy Chinese postmenopausal females: Impacts of a high‐fat meal

Abstract: Progesterone is an important natural hormone regulating ovulation and menstruation. The present study aimed to investigate the pharmacokinetics and safety of two formulations of progesterone in Chinese postmenopausal females under fasting and fed conditions. The study adopted a single‐dose, open‐label, randomized, three‐period bioequivalence design. A total of 96 subjects were enrolled and randomly assigned to the fasting cohort or fed cohort. A high‐fat meal (890 kcal) was used in the fed study. The reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Progesterone (PROG) is an important female hormone, which can protect the fetus, promote pregnancy, and regulate the body temperature center, and is also an important regulator of the nervous system function (122,123). Sharma et al (124) found that PROG (15 mg/kg/d BW by injection) could improve the behavioral cognitive impairment induced by acute or chronic PHOS (1.74 mg/kg/d BW by gavage) exposure in rats.…”
Section: Progesteronementioning
confidence: 99%
“…Progesterone (PROG) is an important female hormone, which can protect the fetus, promote pregnancy, and regulate the body temperature center, and is also an important regulator of the nervous system function (122,123). Sharma et al (124) found that PROG (15 mg/kg/d BW by injection) could improve the behavioral cognitive impairment induced by acute or chronic PHOS (1.74 mg/kg/d BW by gavage) exposure in rats.…”
Section: Progesteronementioning
confidence: 99%